2022
DOI: 10.1101/2022.01.03.474765
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Druggable redox pathways against M. abscessus in cystic fibrosis patient-derived airway organoids

Abstract: Mycobacterium abscessus (Mabs) drives life-shortening mortality in cystic fibrosis (CF) patients, primarily because of its resistance to chemotherapeutic agents. Both our knowledge on and models to investigate the host and bacterial determinants that drive Mabs pathology in CF patients remain rudimentary. Here, we evaluated whether the lung organoid technology from CF patients is appropriate for modelling Mabs infection and whether antioxidant treatment is a candidate therapeutic approach in the context of CF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 88 publications
2
13
0
Order By: Relevance
“…Consistently, we found that NITD-916 was as active as RFB in CF patient-derived AO recapitulating the CF airway dysfunctions, such as thick mucus, and with increased susceptibility to M. abscessus infection. 45 Thus, our data emphasize an unexploited chemical structure class active against M. abscessus infections with promising translational development possibilities for the treatment of CF patients.…”
Section: ■ Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Consistently, we found that NITD-916 was as active as RFB in CF patient-derived AO recapitulating the CF airway dysfunctions, such as thick mucus, and with increased susceptibility to M. abscessus infection. 45 Thus, our data emphasize an unexploited chemical structure class active against M. abscessus infections with promising translational development possibilities for the treatment of CF patients.…”
Section: ■ Discussionmentioning
confidence: 61%
“…In this biological model where mycobacteria are injected in AO, M. abscessus was found to actively replicate over 7 days in the lumen, and this was accompanied by reduced expression of mucin genes, usually participating in the clearance of pulmonary pathogens . Moreover, AO derived from CF patients were characterized by low CFTR activity and enhanced mucus accumulation, and the subsequent injection of M. abscessus in these 3D structures revealed the production of biofilms formed by the S variant and serpentine cords formed by the R variant . Importantly, both variants replicated more efficiently in CF AO than in AO derived from healthy lungs, thus highlighting the relevance of this model to study the pathogenesis of M. abscessus and to test the therapeutic potential of compounds in a system that recapitulates a CF environment .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Many studies have scrutinized how M. abscessus behaves in phagocytic cells such as macrophages [29][30][31][32][33][34][35] , and a variety of animal models have been developed for M. abscessus infection [36][37][38][39][40][41][42][43] ; however, these systems often represent systemic or invasive disease, and typically do not recapitulate the extracellular, luminal niche occupied by M. abscessus during human lung infection. Tissue culture systems represent an alternative approach to model lung infection, and can be successfully applied to M. abscessus [44][45][46][47] . Thus, to isolate the role of the lung environment in shaping M. abscessus gene essentiality, we have adapted an air-liquid interface tissue culture model for M. abscessus infection and used genome-wide saturating transposon mutagenesis and sequencing (TnSeq) to identify genes essential for survival in the lung environment.…”
Section: Introductionmentioning
confidence: 99%